2005
DOI: 10.1101/lm.32305
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal inactivation enhances taste learning

Abstract: Learning tasks are typically thought to be either hippocampal-dependent (impaired by hippocampal lesions) or hippocampal-independent (indifferent to hippocampal lesions). Here, we show that conditioned taste aversion (CTA) learning fits into neither of these categories. Rats were trained to avoid two taste stimuli, one novel and one familiar. Muscimol infused through surgically implanted intracranial cannulae temporarily inactivated the dorsal hippocampus during familiarization, subsequent CTA training, or bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 65 publications
2
41
1
Order By: Relevance
“…One possible interpretation of this observation is that competitive interference is present during the post-training period, such that the blockade of consolidation of contextual information allows consolidation of the object information to occur to a greater extent. Previous studies have demonstrated similar competitive interference during memory consolidation (Schroeder et al 2002;Stone et al 2005). Analogous with those findings, another possible interpretation of our results would be that mice either encode object information as part of the context (this situation would occur when objects are presented in an unfamiliar environment) or use a nonspatial strategy in which object information is encoded independent of contextual landmarks.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…One possible interpretation of this observation is that competitive interference is present during the post-training period, such that the blockade of consolidation of contextual information allows consolidation of the object information to occur to a greater extent. Previous studies have demonstrated similar competitive interference during memory consolidation (Schroeder et al 2002;Stone et al 2005). Analogous with those findings, another possible interpretation of our results would be that mice either encode object information as part of the context (this situation would occur when objects are presented in an unfamiliar environment) or use a nonspatial strategy in which object information is encoded independent of contextual landmarks.…”
Section: Discussionsupporting
confidence: 87%
“…Our results further suggest that competitive interference between multiple memory systems may be present during the post-training period (consolidation phase) in the NOR task, as has been observed previously for other memory tasks (for review, see Schroeder et al 2002;Poldrack and Packard 2003;Stone et al 2005;Winters et al 2007). In contrast to the view suggesting a central role for the hippocampal system in memory formation generally, several studies have demonstrated that inactivation of the hippocampal structure does not induce a generalized amnesia, but rather causes impairments in specific types of memory.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…It is clear that the area of insular cortex from which these recordings were made is vital for CTA learning (Stone et al, 2005), which suggests (although does not prove) that late saccharin responses did not merely "move elsewhere" in the brain; the most likely explanation is that sensory processing is as affected by a sudden loss of response as by a sudden increase in response.…”
Section: Discussionmentioning
confidence: 99%
“…Conditioned taste aversion (CTA), a simple learning paradigm whereby a formerly preferred taste becomes unpalatable after being paired with gastric distress (Nachman and Ashe, 1973;Bermudez-Rattoni et al, 1986;Gallo et al, 1992;Rollins et al, 2001), offers a unique window into systems-level properties of learning, because it vitally involves both basolateral amygdala (BLA) (Nachman and Ashe, 1974;Rollins et al, 2001;Reilly and Bornovalova, 2005;Wang et al, 2006) and gustatory cortex (GC) (Gallo et al, 1992;Berman and Dudai, 2001;Stone et al, 2005), and because the speed with which taste aversions are learned makes it feasible to maintain isolations of single neurons from before until after learning using chronic microwire techniques (Katz et al, 2001b).…”
Section: Introductionmentioning
confidence: 99%